The Frequency Stability Analysis Due to the Integration of 100 MW Solar Power Plant in the 150 kV Power System: A Case Study on the Impact of Large-Scale Solar PV Penetration on Grid Frequency Stability - Davis, Vincentius; Abraham Lomi; Irrine Budi Sulistiawati (SinarFe7, 2025)
This study analyzes the impact of integrating a 100 MW Solar Power Plant (PLTS) (4×25 MW) on the frequency stability of the power system in the 150 kV transmission network in Bali. Simulations were conducted using DIgSILENT PowerFactory software employing Load Flow and RMS Simulation methods, covering disturbance scenarios such as load increases up to 60%, generator outages (Gilimanuk and Pemaron), and the effect of system protection settings. Results show that without proper protection settings, the integration of PLTS leads to a frequency drop below the minimum threshold (47.76 Hz) and a high Rate of Change of Frequency (ROCOF) (-1.21 Hz/s), which poses a risk of system disconnection. After configuring protective relays (underfrequency, undervoltage, and df/dt), the system stability improved; frequency was maintained within the 48–52 Hz range, and ROCOF decreased below -0.5 Hz/s. Therefore, large-scale PLTS integration can be safely implemented without compromising system stability, provided that appropriate protection configurations are in place. This research supports the implementation of clean energy in Bali and serves as a reference for integrating renewable energy sources into existing power systems.